Comparative Analysis of Openpuff and Openstego Tools - Heryanti, Linda; Baihaqi, Wiga Maulana; Habibah, Ariska Nurul; Kusuma, Bagus Adhi (PT Mattawang Mediatama Solution, 2024)
Steganography is the science and art of hiding information in a medium so that its existence is not detected by unauthorized parties. Media that can be used in steganography are text, images, audio, and video. However, the media that is often used is image. Various steganography tools have been developed with their respective strengths and weaknesses, such as Hide in Picture; Openstego; Image Steganography; Invisible Secret 4; S-Tools; Hide 'N' Send; Online Image Steganography, Openpuff, and others. Researchers carried out a comparative analysis of the steganography tools Openpuff and Openstego with test parameters for the quality of the images produced and time efficiency. Test the quality of the resulting image using MSE, PSNR, NCC, SSIM, and time-efficient testing seen from embedding and extraction time. Based on the research results, show that Openstego has better image quality and time efficiency compared to Openpuff. The type of image format used and the size of the embedded message can affect the quality of the resulting image and the time used. The best test results were obtained, namely MSE=0.0009, PSNR=78.5438 dB, NCC=0.999999, SSIM=0.999993, and required embedding time=0.075 second and extraction time=0.084 second. Keywords: Image Quality, Openpuff, Openstego, Steganography, Time.